Legitimasi Ahlussunnah Wal Jama’ah dalam Al-Qur’an dan Hadits: Studi Komprehensif serta Implikasinya dalam Pendidikan (International Forum of Researchers and Lecturers, 2025)
Ahlussunnah Wal Jama’ah (Aswaja) is an Islamic doctrine based on the Qur’an, Hadith, and the understanding of the companions and early scholars. This study aims to examine the Qur’anic and Hadith-based evidence that legitimizes Aswaja and its relevance to Islamic education. The research employs a literature review method, analyzing primary sources such as classical and contemporary tafsir books, major Hadith collections (Sahih Bukhari, Sahih Muslim, Sunan Tirmidhi), and scholarly works by figures like Imam Ash’ari and Al-Ghazali. The findings indicate that Qur’anic verses, such as Surah Al-An’am (6:153) and Surah Ali Imran (3:103), emphasize the importance of adhering to the straight path, which is a central tenet of Aswaja. Furthermore, the Hadith on the division of the Muslim ummah into 73 sects supports Aswaja’s position as al-firqah an-najiyah (the saved sect). These sources provide textual legitimacy to the doctrine of Aswaja, affirming its central role in preserving Islamic unity. The implications for Islamic education are significant, including the integration of Aswaja values into curricula, the promotion of a moderate and balanced understanding of Islam, and the strengthening of faith based on authentic textual evidence. By incorporating Aswaja principles, educators can foster an environment that prioritizes tolerance, inclusivity, and intellectual engagement within Islamic educational settings. This study contributes to reinforcing a moderate and tolerant Islamic approach, promoting a harmonious balance between tradition and modernity in educational contexts.